PENGUATAN KEBIJAKAN PENGENDALIAN MALARIA DI KABUPATEN TOJO UNA-UNA DAN KABUPATEN BANGGAI KEPULAUAN PROVINSI SULAWESI TENGAH - Ningsi Ningsi; Ade Kurniawan; Meiske Elisabeth Koraag; Rina Isnawati (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2020)
Abstract Malaria remained a public health problem at the global level, as well as in Indonesia. In Banggai Islands District and Tojo Una-una District, the API (Annual Parasite Incidence) tends to decrease every year. Village institutions and local community leaders are quite influential in reducing malaria cases. This study aimed to explore the policy reinforcing factors in malaria control, including malaria program policies and the involvement of local institutions in controlling malaria. The type of this study was qualitative with the Rapid Assessment Procedure. Data collection techniques with triangulation through in-depth interviews, Focus Group Discussion, observation, and study of documents. Analysis data use domain analysis. The samples were selected through snowball sampling, consists of community leaders, malaria policy program makers at the district, health center and community who had been diagnosed with malaria. Retrieval of data with triangulation techniques to compared analysis. The results of the study showed that the collaboration between the Banggai Islands and Tojo Una-una District Health Office and the relevant agencies, in resolving malaria elimination as stipulated in the regent's regulations, the stakeholders are still carrying out their respective programs. The policy strengthening factor in malaria control in Tojo Una-una District is the existence of a malaria-free declaration from 2015 by local institutions and local communities, as well as local wisdom of the Banggai Islands District in the form of village race activities as an indicator of public health and environmental sanitation. Abstrak Malaria masih merupakan masalah kesehatan masyarakat di tingkat global, demikian pula di Indonesia. Kabupaten Banggai Kepulauan dan Kabupaten Tojo Una-una memiliki API (Annual Parasite Incidence) cenderung menurun setiap tahunnya. Lembaga desa dan tokoh masyarakat memegang peran penting dalam penurunan kasus malaria. Tujuan penelitian adalah mengeksplorasi faktor penguat kebijakan dalam pengendalian malaria yaitu, kebijakan program malaria dan keterlibatan institusi lokal dalam pengendalian malaria. Jenis penelitian ini adalah kualitatif dengan rancangan Rapid Assessment Procedure. Teknik pengumpulan data dengan triangulasi melalui wawancara mendalam, Focus Group Discussion, observasi dan telaah dokumen. Analisis data menggunakan analisis domain. Pemilihan sampel secara snowball sampling, sampel terdiri dari tokoh masyarakat, penentu kebijakan program malaria di tingkat kabupaten, puskesmas dan masyarakat yang pernah positif malaria. Hasil penelitian menunjukkan kolaborasi antara Dinas Kesehatan Kabupaten Banggai Kepulauan dan Kabupaten Tojo Una-una dengan instansi terkait, dalam pencapaian eliminasi malaria yang tertuang dalam peraturan bupati belum berjalan dengan baik, stakeholder masih menjalankan programnya masing-masing. Faktor penguat kebijakan dalam pengendalian malaria di Kabupaten Tojo Una-una adalah adanya deklarasi bebas malaria tahun 2015 oleh institusi lokal dan masyarakat setempat, serta kearifan lokal pemerintah Kabupaten Banggai Kepulauan berupa kegiatan lomba desa sebagai indikator kesehatan masyarakat dan sanitasi lingkungan.